2021
DOI: 10.33086/ijmlst.v3i1.1848
|View full text |Cite
|
Sign up to set email alerts
|

Ability of Ethanol Extract from Ajwa and Sukkari Dates (Phoenix dactylifera L.) in Inhibiting the Growth of Methicillin-Resistant Staphylococcus aureus (MRSA)

Abstract: Staphylococcus aureus is a pathogenic bacterium that spread throughout the world and still a problem that continues to increase both in hospitals and the community. Infections due to S. aureus usually treated with antibiotics, but in some cases, several strains of S. aureus found to be resistant to antibiotics, such as Methicillin-Resistant Staphylococcus aureus (MRSA). Based on the previous research, the ethanol extract from Ajwa and Sukkari dates formed an inhibitory zone against the MRSA bacteria growth. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
1
0
1
Order By: Relevance
“…Several studies have led to the need to conduct research on the reevaluation of dates, including the research of Masfiyah & Rahayu (2019) which showed that giving a 100% concentration of methanol extract of dates was not able to inhibit the growth of E. colli and K. pneumoniae bacteria, other studies showed that giving the extract Aquades of date palm fruit has not been effective in inhibiting S. aureus bacteria (Ammar et al, 2009;Maged & Abbas, 2013;Saleh & Otaibi, 2013;Al-Zoreky & Al-Taher, 2015;Adedayo et al, 2020;Albab et al, 2020). Another study conducted by Utami et al (2021) also published the same results, namely the ethanol extract of dates was not effective in preventing the reproduction of methicilin Resistant bacteria -Staphylococcus aureus (MRSA).…”
Section: Introductionmentioning
confidence: 68%
“…Several studies have led to the need to conduct research on the reevaluation of dates, including the research of Masfiyah & Rahayu (2019) which showed that giving a 100% concentration of methanol extract of dates was not able to inhibit the growth of E. colli and K. pneumoniae bacteria, other studies showed that giving the extract Aquades of date palm fruit has not been effective in inhibiting S. aureus bacteria (Ammar et al, 2009;Maged & Abbas, 2013;Saleh & Otaibi, 2013;Al-Zoreky & Al-Taher, 2015;Adedayo et al, 2020;Albab et al, 2020). Another study conducted by Utami et al (2021) also published the same results, namely the ethanol extract of dates was not effective in preventing the reproduction of methicilin Resistant bacteria -Staphylococcus aureus (MRSA).…”
Section: Introductionmentioning
confidence: 68%
“…Tingkat signifikan jumlah bakteri dalam urin lebih besar dari 100/ml urin. Bakteri penginfeksian yang paling sering adalah Escheria coli, Proteus Sp, Klebsiella Sp, Serratia, Pseudomonas Sp (Utami et al, 2021) Menurut WHO, infeksi saluran kemih (ISK) adalah penyakit infeksi yang kedua sering di temukan pada tubuh sesudah infeksi saluran pernapasan, sebanyak 8.3 juta kasus di laporkan per tahun. ISK dapat mengenai baik pria maupun wanita dari semua umur baik anak-anak, remaja, dewasa maupun lanjut usia.…”
unclassified